Quantitative methods in project management - Goodpasture, John C. (J. Ross Pub., 2004)
Project success means making the numbers. Project success means delivering business value from the application of resources to project scope and taking measured risks to achieve deliverables. Quantitative methods provide the basis for calculating value, establishing the project metrics that will be the measures of success, and helping project managers understand the numerical values of risks to be addressed.